Social strata and oral pathologies: A comparative study in two co-localized, temporally disjunct burial sites of ancient Egypt - Roger Seiler; Myriam Seco Álvarez; Frank Rühli; Patrick Eppenberger (Elsevier, 2024)
Background/purpose: Oral pathologies in ancient human remains provide a unique glimpse into the lifestyles, health, and societal norms of past civilizations, including ancient Egypt. However, comprehensive paleo-odontological studies accounting for temporal and sociodemographic variations remain scarce. We address this gap by analyzing oral pathologies in the remains of 68 and 57 adult individuals, respectively, unearthed from two adjacent yet temporally and socioeconomically diverse burial sites, representing the XIth dynasty (2160-1985 BCE) and the XXVth-XXVIth dynasties (948-525 BCE), at Luxor's Thutmose III Funerary Temple. Materials and methods: We examined dental wear, carious and periapical lesions, periodontal disease, and temporomandibular joint alterations, hypothesizing that dental wear correlates with age, lifestyle, and diet. We also postulated a link between higher caries frequency and elevated social status and posited the enhanced efficacy of evaluating interdental septa over measuring the alveolar bone-cementoenamel junction distance for periodontitis assessment. Results: Our findings confirm pronounced dental wear in both sites, with the XIth dynasty showing more severe wear, indicating differing dietary habits. While similar across the younger age groups, the later dynasties showed a significantly higher caries frequency than the XIth dynasty, in the older age groups. Furthermore, our results underscore the superior accuracy of evaluating interdental septa for periodontal disease assessment. Conclusion: Variations in oral health, sociodemographic, and dietary trends across the studied burial sites, deepen our understanding of human health trajectories. Additionally, our methodology emphasizes paleo-odontology's vital role in deciphering the nuanced health-environment relationship in ancient societies, laying a foundation for subsequent investigations.